Нанокомпозиты внедрения с высоким содержанием минеральной компоненты - Федоренко, Ю.Г.; Розко, А.Н.; Туронок, О.Ч.; Дяченко, Е.В. (Мінералогічний журнал, 2010)
Приведена информация о синтезе глинополимерных нанокомпозитов, содержащих более 50 % бентонитовой
глины, а также об особенностях свободного набухания частиц нанокомпозитов. В результате замещения Ca²⁺ и
Mg²⁺ ионом Na⁺ в структуре монтмориллонита молекулы акриламида легче входят в межслоевое пространство
кристаллитов этого минерала, формируя нанокомпозит внедрения. Частицы последнего имеют степень набухания в воде более 100 г/г и длительное время сохраняют свойство набухания при циклическом высушивании. Наведено інформацію щодо синтезу глинополімерних нанокомпозитів, що містять понад 50 % бентонітової глини, а також щодо особливостей вільного набухання частинок нанокомпозитів. Унаслідок заміщення Ca²⁺ та Mg²⁺ іонами Na⁺ у структурі монтморилоніту молекули акриламіду легше входять до міжшарового простору кристалітів цього мінералу, утворюючи нанокомпозит проникнення. Ступінь набухання його частинок перевищує 100 г/г, вони тривалий час здатні зберігати властивість до набухання у випадку періодичного
висушування. The practical interest to (nano)composites with high mineral component content (clay) results from its low
price, wide spectrum of rheological characteristics, possibility to change some features of these materials by adding
functional agents during the synthesis.
In the present work characteristics of synthesis of polyacrylamide-clay nanocomposites containing over 50 % of natural
or activated bentonite clays (bentonites) from Cherkasy bentonite and palygorskite deposit in Ukraine were studied.
The organic component was presented by acrylamide (China), the cross-linking agent by N,N’-methylene-bisacrylamide;
acid-reductive conditions for free radical polymerization were formed by adding persulfate ammonium and
ascorbic acid.
The bentonite : water ratio in the source suspensions was 1 : 4, that of bentonite : acrylamide — from 1 : 1 (50 %) to
1.7 : 1 (63 %); N, N ’-methylene-bisacrylamide : acrylamide — from 1 : 22 to 1 : 28. The bentonite suspension activated
by sodium carbonate was neutralized by acrylic acid to рН ~5.5.
The samples were dried, crumbled up and studied by X-ray diffractometry before and after the synthesis. Free swelling
was studied on 15—60 mg particles. The degree of swelling, which was numerically equal to the amount of water taken up
by one gramme of dry nanocomposite particles, was calculated.
The X-ray data revealed that molecules of acrylamide in the source suspensions substitute Ca²⁺ and Mg²⁺ cations in
the interlaminar space of crystalline grains of the main mineral of bentonite — montmorillonite as well as Na⁺ cations in
the activated bentonites. In the crystalline grains the interplanar spacing increases to 18.3 Å and after removal of water
from it the interplanar spacing decreases to 17.2 Å. In this case the molecules of acrylamide easier penetrate into the
interplanar spacing and cannot be removed from it by 25-hour drying at 118 ºC.
Crystalline grains of montmorillonite with acrylamide molecules in the interlaminar space are noted not to segregate
but to form a volume polymer mesh forming intrusion nanocomposites during polymerization of the samples. It
considerably increases the ability of the mesh to build up the volume during osmotic penetration of water molecules
into it.
Inverse relationship between the degree of swelling and the size of particles of the nanocomposite was detected. It was
also found that the degree of swelling of the particles dried after first free swelling increases considerably. These properties
may have practical significance for increasing moisture capacity of the studied materials.
Intrusive polyacrylamide-clay nanocomposites based on acrylamide with high content of the mineral component have
the degree of swelling over 100 g/g and durably preserve swelling-drying cyclicity. It allows using nanocomposites for
hydroisolation of flat-slab decks, screening of toxic waste repositories and increasing of moisture capacity of fields, and
building up of productive moisture in soil.